Michael Oakeshott and the Conversation of Modern Political Thought - Plotica, Luke Philip, 1980- (Book collections on Project MUSE., 2015)
One of the seminal voices of twentieth-century political thought, Michael Oakeshott's work has often fallen prey to the ideological labels applied to it by his interpreters and commentators. In this book, Luke Philip Plotica argues that we stand to learn more by embracing Oakeshott's own understanding of his work as contributions to an ever-evolving conversation of humanity. Building from Oakeshott's concept of conversation as an engagement among a plurality of voices "without symposiarch or arbiter" to dictate its course, Plotica explores several fundamental and recurring themes of Oakeshott's philosophical and political writings: individual agency, tradition, the state, and democracy. When viewed as interventions into an ongoing conversation of modern political thought, Oakeshott's work transcends the limits of familiar ideological labels, and his thought opens into deeper engagement with some of the most significant thinkers of the twentieth century, including Ludwig Wittgenstein, Charles Taylor, Michel Foucault, and Hannah Arendt. Attending to these often unexpected or unrecognized affinities casts fresh light on some of Oakeshott's most familiar ideas and their systematic relations, and facilitates a better understanding of the breadth and depth of his political thought. -- from back cover